2015
DOI: 10.15379/ijmst.v2i0.501
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Nanocomposite Membranes for the Pervaporation Separation of Water - Ethanol Azeotropic Mixtures

Thomasukutty Jose,
Soney C George,
Sabu Thomas

Abstract: Bentonite nanoclay reinforced Poly (vinyl alcohol) (PVA) nanocomposite membranes were used for the separation of azeotropic composition of water – ethanol mixtures by pervaporation process. Fourier – transform infrared (FTIR) spectroscopic studies revealed the interaction of bentonite nanoclay and the PVA matrix. The dispersion and distribution of nanoclay in the polymer matrix was demonstrated by transmission electron microscopic analysis (TEM). The intrinsic membrane properties with filler loading were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Thus, the study of surface properties (in particular, roughness) is useful for the understanding of membrane performance [69]. It was found that the increase in surface roughness parameters of membranes led to the permeability rise due to an increase in the effective membrane area for contact with feed components [70], resulting to their faster sorption and penetration [71]. This effect was also confirmed for membranes from other polymers [71,72].…”
Section: Investigation Of Membrane Physicochemical Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, the study of surface properties (in particular, roughness) is useful for the understanding of membrane performance [69]. It was found that the increase in surface roughness parameters of membranes led to the permeability rise due to an increase in the effective membrane area for contact with feed components [70], resulting to their faster sorption and penetration [71]. This effect was also confirmed for membranes from other polymers [71,72].…”
Section: Investigation Of Membrane Physicochemical Propertiesmentioning
confidence: 83%
“…It was found that the increase in surface roughness parameters of membranes led to the permeability rise due to an increase in the effective membrane area for contact with feed components [70], resulting to their faster sorption and penetration [71]. This effect was also confirmed for membranes from other polymers [71,72]. Surface topography of membranes were evaluated by the calculation of the average (R a ) and root-mean-squared (R q ) roughness based on the obtained AFM images (Table 2).…”
Section: Investigation Of Membrane Physicochemical Propertiesmentioning
confidence: 99%